Acute and late effects of combined internal and external radiation exposures on the hematopoietic system. (2nd November 2019) - Calvi, Laura M.; Frisch, Benjamin J.; Kingsley, Paul D.; Koniski, Anne D.; Love, Tanzy M.; Williams, Jacqueline P.; Palis, James
Abstract: Purpose: Incidents, such as nuclear facility accidents and the release of a 'dirty bomb', might result in not only external irradiation of personnel, but additional internal exposures through concomitant inhalation and/or ingestion of radioactive particulates. The purpose of this study was to define the impact of such a combination of radiation injuries on the hematopoietic niche. Material and methods: To assess changes in the murine hematopoietic system, we used a combined exposure of total body irradiation (TBI, 6 Gy) followed immediately by an internal (intraperitoneal) administration of 100 µ Ci of soluble 137 Cs. We then evaluated acute survival in combined versus single modality exposure groups, as well as assessing hematopoietic function at 12 and 26 week time points. Results: Acutely, the combination of external and internal exposures led to an unexpected delay in excretion of 137 Cs, increasing the absorbed dose in the combined exposure group and leading to mortality from an acute hematopoietic syndrome. At 12 weeks, all exposure paradigms resulted in decreased numbers of phenotypic hematopoietic stem cells (HSCs), particularly the short-term HSCs (ST-HSC); long-term HSCs (LT-HSC) were depleted only in the internal and combined exposure groups. At 26 weeks, there was significant anemia in both the TBI alone and combined exposure groups. There were decreased numbers in both the LT- and ST-HSCs and decreased functionality, as measured by competitive repopulation, was seen in all radiation groups, with the greatest effects seen in the internal and combined exposure groups. Conclusions: Our data indicate that a combined injury of sublethal external irradiation with internal contamination induces significant and persistent changes in the hematopoietic system, as may have been predicted from the literature and our own group's findings. However, a novel observation was that the combined exposure led to an alteration in the excretion kinetics of the internal contamination, increasing the acute effects beyond those anticipated. As a result, we believe that a combined exposure poses a unique challenge to the medical community during both the acute and, possibly, delayed recovery stages.